Exploring the true burden of a time-loss injury: full vs partial time-loss in elite academy football (soccer) - Veith, S.; Whalan, M.; Gibson, N., Sampson, J. A. (Science and Medicine in Football, 2024)
In football, the number of days without full participation in training/competition is often used as a surrogate measure for time-loss (TL) caused by injury. However, injury management and return-to-play processes frequently include modified participation, which to date has only been recorded through self-reports. This study aims to demonstrate the differentiation between `full` (no participation in team football) and `partial` (reduced/modified participation in team football) burden. Injury and exposure data were collected from 118 male elite footballers (U13-U18) over 3 consecutive seasons according to the Football Consensus Statement. TL injury burden was calculated separately as the number of total, `full` and `partial` days lost per 1000 h of exposure. Injury burden (137.2 days lost/1000 h, 95% CI 133.4-141.0) was comprised of 23% (31.9 days lost/1000 h, 95% CI 30.1-33.8) partial TL and 77% (105.3 days lost/1000 h, 95% CI 102.0-108.6) full TL burden. Injuries of moderate severity (8-28 days lost) showed 40% of partial TL. TL injury incidence rate (6.6 injuries/1000 h, 95% CI 5.8-7.5), the number of severe injuries (16%), and the distribution of TL and non-TL injuries (56% and 44%) were comparable to other reports in elite youth footballers. Almost one-quarter of the TL injury burden showed that injured players were still included in some team football activities, which, for injuries with TL >7 days, was likely related to the return to play process. Therefore, reporting on partial TL provides insight into the true impact of injury on participation levels.